circRNA CDR1as Promotes Pulmonary Artery Smooth Muscle Cell Calcification by Upregulating CAMK2D and CNN3 via Sponging miR-7-5p - Cui Ma; Rui Gu; Xiaoying Wang; Siyu He; June Bai; Lixin Zhang; Junting Zhang; Qian Li; Lihui Qu; Wei Xin; Yuan Jiang; Fei Li; et al. (Elsevier, 2020)
Emerging evidence has suggested that circular RNAs (circRNAs) are involved in multiple physiological processes and participate in a variety of human diseases. However, the underlying biological function of circRNAs in pulmonary hypertension (PH) is still ambiguous. Herein, we investigated the implication and regulatory effect of a typical circRNA, CDR1as, in the pathological process of vascular calcification in PH. Human pulmonary artery smooth muscle cell (HPASMC) calcification was analyzed by western blotting, immunofluorescence, alizarin red S staining, alkaline phosphatase activity analysis, and calcium deposition quantification. CDR1as targets were identified by bioinformatics analysis and validated by dual-luciferase reporter and RNA antisense purification assays. We identified that CDR1as was upregulated in hypoxic conditions and promoted a phenotypic switch of HPASMCs from a contractile to an osteogenic phenotype. Moreover, microRNA (miR)-7-5p was shown to be a target of CDR1as, and calcium/calmodulin-dependent kinase II-delta (CAMK2D) and calponin 3 (CNN3) were suggested to be the putative target genes and regulated by CDR1as/miR-7-5p. The results showed that the CDR1as/miR-7-5p/CNN3 and CAMK2D regulatory axis mediates HPASMC osteoblastic differentiation and calcification induced by hypoxia. This evidence reveals an approach to the treatment of PH.